Development of an Orientation-independent Handheld Nebulizer - Sheng-Hsiu Huang; Chih-Wei Lin; Wei-Ren Ke; Yu-Mei Kuo; Chih-Chieh Chen (Aerosol and Air Quality Research)
Abstract This work aimed to develop and evaluate a miniaturized handheld vibrating mesh nebulizer (MHVMN) that functions equally well in any orientation. The MHVMN, which comprises a a power supply unit, a vibrating mesh plate, and a liquid reservoir equipped with either a flat end orifice tube (FEOT) or a traditional wick for delivery, was primarily tested using deionized water and a 0.9% sodium chloride solution. Since our study focused on optimizing the dimensions of the FEOT, which utilizes capillary action to deliver the solution, we examined the effects of the operating parameters, viz., the gap between the reservoir wall and the FEOT (LLR-FEOT), the diameter of the FEOT’s orifice (Dorifice), the orientation of the nebulizer, and the size of the aperture, on the performance of the device. The output rate and the residual volume were determined gravimetrically, and both the concentration and the mass distribution of the aerosolized particles were measured with an aerosol size spectrometer (welas digital 3000) and a Micro-Orifice Uniform Deposit Impactor (MOUDI). The results revealed an optimal LLR-FEOT of 0.225 mm, which achieved similar output rates and residual volumes across various orientations. Additionally, a Dorifice exceeding 0.8 mm was necessary to ensure continuous nebulization, thereby yielding a residual volume of less than 4%. Using the FEOT instead of a traditional wick also significantly decreased the residual volume—a major advantage in delivering costly drugs. The consistently high efficiency of the MHVMN regardless of orientation demonstrates its suitability for administering aerosolized medication, especially to patients lying in bed.